Prospect and challenges of glass container industry in Bangladesh: an empirical study on selected glass container industry of Bangladesh - Hossain, Zakir (BRAC University, 2015)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2014.